The interplay between EU competition law and intellectual property rights - analysis of tying and bundling practices by dominant undertakings - Koļesņikova, Zane (Riga Graduate School of Law, 2019)
This thesis discusses tying and bundling, practices of a sale of two or more distinct products, which are common in various types of markets. When dominant undertakings have tied or bundled patented goods or technologies, such practices have resulted in substantial fines and findings of abuse of dominant position under Article 102 TFEU. Thus, the author aims to examine the interplay between EU competition law and IPRs, notably possible effects on competition and consistency in the CJEU’s reasoning. While tying was originally applied to contractual obligations, the scope of application has been broadened to technical integration in the landmark Microsoft case. Research implies that tying or bundling may create both efficiency gains and strategic reasons (entry barriers, competitive advantage)– dependence on Chicago or post-Chicago economic models may influence the enforcement by competition authorities.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Competition law